2018
DOI: 10.1115/1.4041777
|View full text |Cite
|
Sign up to set email alerts
|

Triangular Mesh and Boundary Representation Combined Approach for 3D CAD Lightweight Representation for Collaborative Product Development

Abstract: The lightweight representation of three-dimensional computer-aided design (3D CAD) models has drawn much attention from researchers as its usefulness in collaborative product development is vast. Existing approaches are mostly based on feature depression or mesh-based simplification. In this article, a new approach for 3D CAD lightweight representation based on combining triangular mesh representation and boundary representation (B-rep) is proposed. The corresponding data structure as well as the conversion me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A way to reduce this computation time is to let the CAD Kernel compute the tessellation and export the result to X3D as a mesh node among all available (IndexedFaceSet, IndexedTriangleSet, TriangleSet etc.). This solution dispenses the viewer with the computation before rendering, thus resulting in a performance gain [Nguyen, 2019]. However, it comes with a semantic loss because the mesh, regardless of the precision, can only be an approximated representation of the surface.…”
Section: Nurbs Curves and Surfaces For Exact Geometry Conversion Rmentioning
confidence: 99%
“…A way to reduce this computation time is to let the CAD Kernel compute the tessellation and export the result to X3D as a mesh node among all available (IndexedFaceSet, IndexedTriangleSet, TriangleSet etc.). This solution dispenses the viewer with the computation before rendering, thus resulting in a performance gain [Nguyen, 2019]. However, it comes with a semantic loss because the mesh, regardless of the precision, can only be an approximated representation of the surface.…”
Section: Nurbs Curves and Surfaces For Exact Geometry Conversion Rmentioning
confidence: 99%
“…The basic shapes such as box, cylinder, sphere, cone, and pyramid are smaller in size than representing them using triangular meshes, because not only the parameter information, but also information such as dimension and position is stored. With regard to this, Nguyen et al [18] proposed a method for reducing the size of lightweight models by representing a triangular mesh model and a B-rep model in hybrid. Furthermore, Eigner et al [19] suggested a method for using the JT file together with an XML file that contains additional information in order to improve the utilization of the JT file.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…This is because the shape can be configured by combining the stored data simply with no additional complex computations for restoration. Conventional methods to store a lightweight model can be categorized into the following three categories: the method to store a 3D shape as triangular mesh [23], the method to store only parameter values needed to define primitives which are used to represent a 3D shape [12], and the method to store both triangular mesh and B-rep elements [18]. The first method requires no additional work other than creating a triangular mesh from a 3D CAD model, but the file size is large.…”
Section: Implementation and Experimentsmentioning
confidence: 99%
“…An important task is to make a bridge between the 3D design software and teaching software (CNN frame-work). The research related to 3D design can be found in various papers, e.g., about parameter enhancement in a 3D model [15], 3D CAD (Computer Aided Design) lightweight representation [16], or design process automation [17]. The automated sample generation from 3D models can be simplified using a web interface.…”
Section: Introductionmentioning
confidence: 99%